Effect of filler load on structural coloration and color adjustment potential of resin composites - Furusawa, Kiyoka; Kobayashi, Shun; Yamashita, Ako; Tichy, Antonin; Hosaka, Keiichi; Shimada, Yasushi; Nakajima, Masatoshi (Dental materials journal, 2023)
The color-matching ability of single-shade composites Omnichroma (OMN) and Omnichroma Flow (OCF) is ensured by structural color, which arises from monodisperse 260 nm spherical fillers. This study evaluated how filler load influences the color adjustment potential of composite restorations to human teeth of various shades. The performance of composites containing the 260 nm spherical fillers -OMN (79 wt%), OCF (71 wt%), and experimental composites R1 (65 wt%), and R2 (60 wt%)- was compared to two conventional A2-shade composites and a transparent composite. Additionally, the translucency parameter, spectral reflectance, and light transmission properties were assessed. Composites with a lower load of the 260 nm spherical fillers exhibited lower light diffusion and lower reflectance in the yellow-to-red range (580-650 nm), which is characteristic for the structural color of OMN and OCF. The best color adjustment was achieved with OCF, presumably due to its high translucency and uniform spectral reflectance.
Keywords: Humans; lidé; testování materiálů; Composite Resins; složené pryskyřice; Materials Testing; Color; barva